COPD Assessment Test (CAT) is a Valid and Simple Tool to Measure the Impact of Bronchiectasis on Affected Patients. (3rd September 2018) - Lanza, Fernanda C.; Castro, Rejane A. S.; de Camargo, Anderson A.; Zanatta, Drielly J. M.; Rached, Samia; Athanazio, Rodrigo; Cukier, Alberto; Stelmach, Rafael; Dal Corso, Simone
Abstract: The COPD assessment test (CAT) is a short questionnaire developed to help patients and clinicians to assess the impact of symptoms in routine clinical practice. We aimed to validate and to test the reproducibility of CAT in patients with bronchiectasis and correlate with the severity of dyspnea, aerobic and functional capacity, and physical activity in daily life. This is a cross-sectional study, patients with bronchiectasis underwent spirometry, cardiopulmonary exercise test (CPET), incremental shuttle walk test (ISWT), Saint George`s Respiratory Questionnaire (SGRQ), and received pedometer. CAT was applied twice (CAT-1 and CAT-2, 7 to 10 days apart). The severity of bronchiectasis was assessed by E-FACED and bronchiectasis severity index (BSI). A total of 100 patients were evaluated (48 ± 14 years, 59 women, FVC: 67 ± 22% pred, FEV1 : 52 ± 25% pred). According to CAT, 14% patients presented low, 40% medium, 32% high, and 14% very high impact. The higher the CAT, the worse the severity of bronchiectasis, dyspnea, quality of life, performance on the CPET, and smaller the distance walked (DW) on the ISWT and number of steps (NS) per day. There was significant correlation between CAT and SGRQ, E-FACED, BSI, NS, ISWT, oxygen uptake, and workload at CPET. CAT-1 and CAT-2 presented similar values: 21 (13–26) and 19 (13–26), respectively. The CAT is a valid and reproducible instrument in patients with bronchiectasis presenting good correlation with clinical, functional, and quality of life measurements. This easy-to-use, easy-to-understand, quick, and useful tool may play an important role to assess the impact of bronchiectasis on both daily medical practice and clinical trial settings.